Clinical manifestations of sickle cell disease in India: misconceptions and reality. Issue 3 (May 2018) - Jain, Dipty; Mohanty, Dipika
Abstract : Purpose of review: In the past, milder clinical manifestations of sickle cell disease (SCD) have been described from India. However, recent data from some parts of India suggest that the severity of the disease can be compared to that of African phenotypes. This review therefore describes the varied clinical manifestation of SCD, the success of newborn screening programme, prenatal diagnosis and low dose hydroxyurea therapy in India. Recent findings: The varied clinical manifestations such as anemia, vaso-occlusive crisis, acute chest syndrome, renal involvement, stroke and so on vary from one part of the country to the other and also among different communities of India. Strategies for improving quality of life and controlling of SCD have been suggested. Certain factors other than genetics also play an important role in clinical manifestation of the disorder. Summary: The clinical diversity of SCD is described. The natural history of SCD in India is unfolding from newborn screening programme. The use of low-dose hydroxy urea therapy both in adults and children has brought down the incidences of crisis and provides great relief to the patients. The tailor-made programme for India as regards the control and management has been discussed.